The Effect of Scaffolding and Creative Thinking Skills in an Acid and Base Learning Project on Students’ Science Process Skills - Tri Haryati; Muhammad Rusdi; Rayandra Asyhar; Saprizal Hadisaputra; Muhammad Haris Effendi Hasibuan (Jurnal Penelitian Pendidikan IPA, 2024)
Scaffolding is a strategy given by teachers to guide students to successfully complete learning tasks. Teachers may provide either questioning, cueing, prompting, or explaining and is based on students’ actual ability. The purpose of this study was to investigate the effect of the scaffolding provision and students’ creative thinking skills on students' science process skills (SPS) in a project-based learning (PjBL) about acid and base concepts. A quasy factorial experiment research design was applied to collect data using a pre-validated SPS-observation. An experiment group from SMAN 3 in Jambi City had learnt the concepts using a scaffolding-assisted PjBL while a control group from the same school had learnt it using PjBL without scaffolding. Prior to the learning, creative thinking ability of the students was measured using a questionnaire. Data was then analyzed using a two-way Anova test assisted by SPSS software. The results of analyses showed that there was an effect of the scaffolding and the creative thinking ability on the students’ SPS. Potential interaction between those variables was also seen in affecting the SPS. It appears that the the presence of scaffolding and the initial students’ ability in creative thinking sinergetically improved the students’ SPS.